2014
DOI: 10.1080/13607863.2014.967659
|View full text |Cite
|
Sign up to set email alerts
|

An RCT to evaluate the utility of a clinical protocol for staff in the management of behavioral and psychological symptoms of dementia in residential aged-care settings

Abstract: These results demonstrate the effectiveness of the BPSD protocol in reducing BPSD and improving staff self-efficacy and stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 24 publications
3
62
0
Order By: Relevance
“…Training for healthcare professionals in dealing with BPSD leads to improvements in the symptoms of people with dementia disease [37] [38]. When healthcare professionals received training, exercise and equipment in the form of a structured BPSD protocol the result was improvements in behavioral symptoms in people with dementia.…”
Section: Education/training For Healthcare Professionalsmentioning
confidence: 99%
“…Training for healthcare professionals in dealing with BPSD leads to improvements in the symptoms of people with dementia disease [37] [38]. When healthcare professionals received training, exercise and equipment in the form of a structured BPSD protocol the result was improvements in behavioral symptoms in people with dementia.…”
Section: Education/training For Healthcare Professionalsmentioning
confidence: 99%
“…82 A recent literature review on the effectiveness of staff training for BPSD 60 also indicated some promise for the content of the training and intervention approach we adopted, as did a recent study of clinical algorithm-based protocols for the management of CB in dementia. 311 However, we additionally chose to develop an online intervention, as we were keen to widen the scope of use in the real world of the full range of 'good-quality' (as rated at the time by the CQC) care home settings. We anticipated that ready access to knowledge and resources available for all staff and practitioners who delivered formal care to people with dementia living at home and in care homes would be a way of sustaining ongoing intervention for dementia with CB.…”
Section: Limitationsmentioning
confidence: 99%
“…Rationale for the intervention Previous work, 63 and more recent studies, 97,311 demonstrated the successful use of algorithm-based protocols in the management of CB in care homes. One of the most recent studies 311 used a pencil-andpaper workbook format in care homes.…”
mentioning
confidence: 99%
See 2 more Smart Citations